Niches for the Long-Term Maintenance of Tissue-Resident Memory T Cells - Takamura, Shiki (Frontiers in Immunology, 2018)
Tissue-resident memory T cells (TRM cells) are a population of immune cells that reside in the lymphoid and non-lymphoid organs without recirculation through the blood. These important cells occupy and utilize unique anatomical and physiological niches that are distinct from those for other memory T cell populations, such as central memory T cells (TCM cells) in the secondary lymphoid organs and effector memory T cells (TEM cells) that circulate through the tissues. CD8+ TRM cells typically localize in the epithelial layers of barrier tissues where they are optimally positioned to act as sentinels to trigger antigen-specific protection against reinfection. CD4+ TRM cells typically localize below the epithelial layers, such as below the basement membrane, and cluster in lymphoid structures designed to optimize interactions with antigen presenting cells upon reinfection. A key feature of TRM populations is their ability to be maintained in barrier tissues for prolonged periods of time. For example, skin CD8+ TRM cells displace epidermal niches originally occupied by T cells, thereby enabling their stable persistence for years. It is also clear that the long-term maintenance of TRM cells in different microenvironments is dependent on multiple tissue-specific survival cues, although the specific details are poorly understood. However, not all TRM persist over the long term. Recently we identified a new spatial niche for the maintenance of CD8+ TRM cells in the lung, which is created at the site of tissue regeneration after injury (termed repair-associated memory depots; RAMD). The short-lived nature of RAMD potentially explains the short lifespans of CD8+ TRM cells in this particular tissue. Clearly, a better understanding of the niche-dependent maintenance of TRM cells will be important for the development of vaccines designed to promote barrier immunity. In this review, we discuss recent advances in our understanding of the properties and nature of tissue-specific niches that maintain TRM cells in different tissues.